2020
DOI: 10.3389/fnins.2020.600839
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Dynamics of Visually Induced Motion Perception and Neural Evidence of Alterations in the Motion Perception Process in an Immersive Virtual Reality Environment

Abstract: Even though reciprocal inhibitory vestibular interactions following visual stimulation have been understood as sensory-reweighting mechanisms to stabilize motion perception; this hypothesis has not been thoroughly investigated with temporal dynamic measurements. Recently, virtual reality technology has been implemented in different medical domains. However, exposure in virtual reality environments can cause discomfort, including nausea or headache, due to visual-vestibular conflicts. We speculated that self-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Theta and alpha bands showed inconsistent results. In particular, while several studies showed enhanced alpha power in the higher cybersickness condition (Ahn et al 2020;Oh and Whangbo 2018), other experiments indicated the opposite result (Celikcan 2019;Chang et al 2013;Choi et al 2009). While beta frequency band tended to show a negative correlation between their power and the level of discomfort (Chang et al 2013;Choi et al 2009;Heo and Yoon 2020;Kim et al 2005), gamma band indicated a positive correlation (Lin et al 2018;Oh and Whangbo 2018).…”
Section: Feature Extractionmentioning
confidence: 85%
See 2 more Smart Citations
“…Theta and alpha bands showed inconsistent results. In particular, while several studies showed enhanced alpha power in the higher cybersickness condition (Ahn et al 2020;Oh and Whangbo 2018), other experiments indicated the opposite result (Celikcan 2019;Chang et al 2013;Choi et al 2009). While beta frequency band tended to show a negative correlation between their power and the level of discomfort (Chang et al 2013;Choi et al 2009;Heo and Yoon 2020;Kim et al 2005), gamma band indicated a positive correlation (Lin et al 2018;Oh and Whangbo 2018).…”
Section: Feature Extractionmentioning
confidence: 85%
“…These locations are well-known places for the reference electrode because they are electrically stabilized but linked to the cortical area. In some cases, a particular spherical region, such as the frontal or parietal area, was chosen for the re-referencing (Ahn et al 2020;Khoirunnisaa et al 2018;Wu et al 2020).…”
Section: Preprocessingmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a study confirmed a reduced visual–vestibular interaction in monkeys using visual motion stimulation ( Chen et al, 2011 ), and nausea reduced connectivity between the right and left V1 ( Toschi et al, 2017 ). The tendency to feel motion sickness decreased with a lowered gap between the left and right using a simulator and tDCS ( Arshad et al, 2015 ; Ahn et al, 2020 ). Therefore, our study showed that cybersickness reduced the connectivity of the visual–vestibular network as confirmed earlier by the microstate analysis, which is consistent with the results of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Because of cybersickness, the participants showed impaired response inhibition and changes in the N2 and P3 components. In Ahn et al (2020), the participants watched 200 trials of short VR scenes (6 s) consisting of an accelerated or constant velocity under EEG recording. The results indicated increased P3 amplitudes during the viewing of accelerated moving conditions, albeit this was only for the participants who reported more severe discomfort.…”
Section: Previous Findings In Cybersickness-related Eegmentioning
confidence: 99%